2024
DOI: 10.1002/btm2.10637
|View full text |Cite
|
Sign up to set email alerts
|

In situ light‐activated materials for skin wound healing and repair: A narrative review

Jordan R. Yaron,
Mallikarjun Gosangi,
Shubham Pallod
et al.

Abstract: Dermal wounds are a major global health burden made worse by common comorbidities such as diabetes and infection. Appropriate wound closure relies on a highly coordinated series of cellular events, ultimately bridging tissue gaps and regenerating normal physiological structures. Wound dressings are an important component of wound care management, providing a barrier against external insults while preserving the active reparative processes underway within the wound bed. The development of wound dressings with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 146 publications
0
19
0
Order By: Relevance
“…The copper bulk concentration in the investigated samples after the performed washing (in accordance with the EN ISO 105-C06:2010 standard [118]) is lower; however, the cooper coatings are still present on the surface of the wool fabric. For the WO-Cu (5) (0.06) sample, the copper bulk content lowered to ~85% of the original value, for the WO-Cu (10) (0.14) to ~88% of the initial bulk concentration, and for the sample WO-Cu (15) (0.38) to ~86% of the copper bulk content prior to the washing. Therefore, it may be concluded that the functionalized samples exhibit a satisfactory washing fastness.…”
Section: Physico-chemical Characteristic Of Wo-cu Materials 321 Atomi...mentioning
confidence: 95%
See 4 more Smart Citations
“…The copper bulk concentration in the investigated samples after the performed washing (in accordance with the EN ISO 105-C06:2010 standard [118]) is lower; however, the cooper coatings are still present on the surface of the wool fabric. For the WO-Cu (5) (0.06) sample, the copper bulk content lowered to ~85% of the original value, for the WO-Cu (10) (0.14) to ~88% of the initial bulk concentration, and for the sample WO-Cu (15) (0.38) to ~86% of the copper bulk content prior to the washing. Therefore, it may be concluded that the functionalized samples exhibit a satisfactory washing fastness.…”
Section: Physico-chemical Characteristic Of Wo-cu Materials 321 Atomi...mentioning
confidence: 95%
“…The evaluation of the copper bulk concentration in wool-copper materials was performed with the use of the FAAS method and is presented in Table 4. (5) (0.06) 2990 0.05 WO-Cu (10) 10 9020 0.14 WO-Cu (10) The copper bulk content in the WO-Cu samples depends on the applied sputtering deposition time, and the correlation bewteen the copper bulk content and the deposition time is almost linear: 5 min process-3510 mg/kg (WO-Cu (5) (0.06)); 10 min process-9020 mg/kg (WO-Cu (10) (0.14)); 15 min process-24,270 mg/kg (WO-Cu (15) (0.38)). In addition, the distribution of copper in a WO-Cu material's bulk after the magnetron sputtering process is uniform.…”
Section: Physico-chemical Characteristic Of Wo-cu Materials 321 Atomi...mentioning
confidence: 99%
See 3 more Smart Citations